2016
DOI: 10.1039/c6ra05152a
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study on the thermodynamics and mechanism of carbon dioxide capture by CaO and CaO regeneration

Abstract: The bond length between the C atom in CO2 and O atom in CaO was about 1.39–1.42 Å, and the bond length of C–O in adsorbed CO2 was prolonged to 1.26–1.27 Å, while the O–C–O angle of adsorbed CO2 was about 129°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 44 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…(b) and (c), a shift to the highest binding energy of Ca 2p and O 1s in C‐Mn‐CaO was found, which was not observed in the original CaO. It means that it was easier for the Ca atom and O atom in C‐Mn‐CaO to give electrons to CO 2 than the original CaO, which assisted the fast formation of CO 3 . The doping of Mn in CaO was beneficial to the electron transport from CaO to CO 2 , which accelerated the carbonation rates of CaO.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…(b) and (c), a shift to the highest binding energy of Ca 2p and O 1s in C‐Mn‐CaO was found, which was not observed in the original CaO. It means that it was easier for the Ca atom and O atom in C‐Mn‐CaO to give electrons to CO 2 than the original CaO, which assisted the fast formation of CO 3 . The doping of Mn in CaO was beneficial to the electron transport from CaO to CO 2 , which accelerated the carbonation rates of CaO.…”
Section: Resultsmentioning
confidence: 93%
“…. Sun et al . presented the formation processes of CO 3 2− : the electrons were transferred from the Ca atom or other atoms to the O atom on the surfaces of the sorbents first, and then the electrons were transferred from the O (CaO surface) atom to the C atom in CO 2 , then to the O atom in CO 2 in the carbonation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Although the Li promoter can enhance the strength of CO 2 adsorption remarkably, CO 2 needs to be desorbed from the adsorbent. , Therefore, the adsorption strength of CO 2 on a MgO–CaO(100) solid-solution surface should be weaker than its thermodynamic criteria. Because there are no available reports on the enthalpy of the most related reaction (MgO–CaO + CO 2 ↔ MgCaCO 3 ), this study used the enthalpy of 1.85 eV (178 kJ/mol) in the reaction, CaO + CO 2 ↔ CaCO 3 . , To explore the dopant effect on CO 2 adsorption, the Li-promoted MgO–CaO(100) surface was doped with Sr. Four possible dopant sites exist (Figure ). Among these, configuration II was the most stable Sr dopant site.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 For example, the carbonation and calcination of CaO has been widely studied. 28 Sun et al 29 and He et al 30 found that the carbonation reactivity of CaO is closely related to the electron transfer between the C atom and the surface O atom in CaO from DFT analysis. Guo et al 31 calculated the electron characteristics of CO 2 adsorbed on a CaO (100) surface.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the s, p states of the surface O atom and the C atom contribute towards stable bonding between CO 2 and CaO. Sun et al 29 studied the reaction between CO 2 and CaO in the framework of DFT. Simulation of the transition states during carbonation and calcination show that CO 2 adsorption by CaO is rather fast and that the rate of CO 2 desorption is controlled by the chemical reaction.…”
Section: Introductionmentioning
confidence: 99%